THE IMPROVEMENT AND APPLICATION OF EI-GUN (ELECTRICAL INSEMINATION GUN) FOR ARTIFICIAL INSEMINATION (AI) USING GOAT FRESH SEMEN - Mirsa Ita Dewi; Gatot Ciptadi; Lilik Eka Radiati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2016)
Electrical Insemination Gun (EI-GUN) was a tool for Artificial Insemination (AI) using fresh semen with an electric control system. The research objective was to produced EI-GUN for AI using fresh semen on small ruminants (goat). The research was conducted from March to June 2015. The process of EI-GUN creation implemented in Design and Prototype Laboratory and Aero Modeling Research Laboratory at Engineering Faculty, University of Brawijaya (UB). Testing tools EI-GUN on goat was conducted in the Sumber Sekar Laboratory, Animal Husbandry Faculty, UB. The methods of research were literature study, tool specification determination, designing EI-GUN, running test, semen evaluation passed EI-GUN and application on Goat. EI-GUN has seven important parts, which supports each other in this operating system. Those parts consist of stylet, servo, system controlled, insemination pump, connecting rod, battery, and holder. EI-GUN work system sucked the semen into insemination pump as much as 5 ml, and release the semen 0.25 ml appropriate standard of AI. It was applicable for 20 times AI. The results showed that the cell motility of spermatozoa ≥ 70% were still in ranging of Indonesian National Standard (SNI). Keywords: artificial insemination, EI-GUN, fresh semen.